1996
DOI: 10.1038/bjc.1996.216
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignant melanoma in relation to drug intake, alcohol, smoking and hormonal factors

Abstract: Risk of malignant melanoma in relation to drug intake, alcohol, smoking and hormonal factors J Westerdahl', H Olsson2, A Masback3, C Ingvar' and N Jonsson3 Departments of 'Surgery, 2Oncology, 3Pathology, University Hospital, S-22J85 Lund, Sweden.Summary In a population-based, matched case-control study from southern Sweden of 400 patients with a first diagnosis of malignant melanoma and 640 healthy control subjects aged 15-75 years, the association between commonly prescribed drugs, alcohol, smoking and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
91
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 27 publications
(39 reference statements)
8
91
2
2
Order By: Relevance
“…However, subsequent research has not generally supported this finding (Helmrich et al, 1984;Holman et al, 1984;Gallagher et al, 1985;Osterlind et al, 1988b;Zanetti et al, 1990;Hannaford et al, 1991;Palmer et al, 1992;Holly et al, 1995;Westerdahl et al, 1996). Failure to find an association between melanoma and oral contraceptive use may be due to the broad categorization of 'ever users'.…”
mentioning
confidence: 63%
“…However, subsequent research has not generally supported this finding (Helmrich et al, 1984;Holman et al, 1984;Gallagher et al, 1985;Osterlind et al, 1988b;Zanetti et al, 1990;Hannaford et al, 1991;Palmer et al, 1992;Holly et al, 1995;Westerdahl et al, 1996). Failure to find an association between melanoma and oral contraceptive use may be due to the broad categorization of 'ever users'.…”
mentioning
confidence: 63%
“…However, even in these large cohorts, the numbers of exposed and unexposed cases were relatively small (six exposed cases in NHS and eight in NHS II). Two other recent and relatively large case -control studies reported from Connecticut and Sweden (Westerdahl et al, 1996;Smith et al, 1998) observed no relation between ever use or duration of oral contraceptive use and risk of melanoma. But, neither of these studies specifically examined current vs past use of oral contraceptives.…”
Section: Epidemiologymentioning
confidence: 82%
“…However, these findings were based on a relatively small number of cases, and another cohort study found no excess risk (Adam et al, 1981). Subsequent case -control and cohort studies (Bain et al, 1982;Holly et al, 1983Holly et al, , 1995Holman et al, 1984;Helmrich et al, 1984;Beral et al, 1984;Gallagher et al, 1985;Green and Bain, 1985;Østerlind et al, 1988;Zanetti et al, 1990;Hannaford et al, 1991;Le et al, 1992;Palmer et al, 1992;Westerdahl et al, 1996;Gefeller et al, 1998;Smith et al, 1998;Feskanich et al, 1999) provided little evidence of an overall excess risk among ever users compared to never users, but a possible increase among long-term users (summarised in (Prentice and Thomas, 1987)). More recently, data from the Nurse's Health Studies indicated a risk of melanoma related to duration of oral contraceptive use, but only among current users (Feskanich et al, 1999).…”
mentioning
confidence: 99%
“…Experimental studies performed on animals have revealed that UVA can participate in the induction of melanomas (Setlow et al, 1989;Wolf et al, 1994). Furthermore, epidemiological data have shown that exposition to UVA constitutes a risk factor for melanoma (Wang et al, 2001;Westerdahl et al, 2000). UVB also trigger an oxidative reaction, but they predominantly produce DNA lesions (cyclobutane pyrimidine dimers and pyrimidine (6 ± 4) pyrimidone photoproducts) which are recognized by the nucleotide excision repair system.…”
Section: Introductionmentioning
confidence: 99%